Social-Psychological Issues in EFL Speaking Class based on Collaborative Learning - Abdullah Abdullah; Sahril Nur; Ranta Butarbutar; Marni Bawawa (VELES Voices of English Language Education Society, 2023)
Collaborative learning (CL) is relatively a novel approach applied in teaching speaking at the context of English as a foreign language (EFL). Statistically, even if CL has widely been investigated in the field of language teaching, it is still rarely found articles discussing CL issues related to social-psychological perspective. Therefore, this study has the purpose of investigating the variables that influence and are encountered by the student's speaking abilities during cooperation. Five students were used in the research in order to conduct an interview. They were deliberately chosen from their peers because they spoke English the best. Information was acquired through an online interview via the use of the WhatsApp calling app. Additionally, the ATLAS.ti application was used to evaluate the collected data. The results showed that 25 sub-dimensions and three major dimensions: social cognition, relationships, and social behavior significantly affected students' speaking abilities in EFL. The curriculum creator is advised to include social psychology into the English language instruction curriculum nevertheless. It suggests a classroom experiment with planned and unplanned speaking performances for further research.